Biography of a Renaissance Philosopher (Copernicus) and the Relevance of His Thought in the World of Education Today - Junita Putri (MUNTAZAM, 2024)
Education builds a generation with a strong foundation in shaping good moral attitudes and personalities to enhance the well-being of every individual. This is based on the philosophy that emerged and evolved towards the advancement of philosophy. Education provides both spiritual and physical aspects as an effort to self-development and life enrichment. The philosophical thinking, particularly in the Renaissance or early modern period, provided opportunities for progress and sophistication in education. This article aims to elucidate how a philosopher from the Renaissance period had a significant impact on the advancement of education during that era and the relevance of their thinking, such as Copernicus, who promoted knowledge and the science of education. This article requires a method based on a literature review method that utilizes facts and supporting sources to analyze and explore the issue in detail. One of the key philosophers of the Renaissance era was Copernicus. He was a philosopher who had a significant impact on education due to his remarkable thoughts and several works that greatly supported education, and the theories he formulated had a profound influence on various aspects of life. Therefore, it can be concluded that the development of the Renaissance era provided highly valuable aspects for the progress of education. Keywords: Philosophy, Education, Thought, Renaissance, Nicolaus Copernicus